Relationship between functional independence and community integration of people with spinal cord injury in Bangladesh - Das, Shazal Kumar; Bakhtiar, Md; Sabrin, Saiba Muhammad; Curtin, Michael; Rahman, Ehsanur; Nahid, Zahid Bin Sultan; Rahman, Zakia; Haque, Md. Furatul; Patwary, Md. Fazlul Karim; Alam, Md. Jahangir; Hossain, Md. Emran; Rahman, Md. Atiar; et al. (Frontiers in Rehabilitation Sciences, 2024)
DesignProspective, cross-sectional study.ObjectivesTo determine the functional outcome and home and social integration of people who had spinal cord injury and completed their inpatient rehabilitation.SettingCentre for the Rehabilitation of the Paralysed (CRP), Bangladesh.MethodsSpinal Cord Independence Measure (SCIM) and Community Integration Questionnaire (CIQ) were used to analyse the relationship between the functional outcome and home and social integration at the end of rehabilitation. Descriptive and inferential statistics were performed to analyse the data.ResultsA total of two hundred participants (181 men and 19 women) were recruited for the study. Among the participants, 92.5% of them reported a history of trauma or accident, including road traffic accidents, falls and other injuries. Approximately 60% of participants presented with paraplegia and 62.5% of participants were categorized on the ASIA Impairment Scale (AIS) as Grade A, complete spinal cord injury. Participants with paraplegia and participants with a Grade B, incomplete injury, on the AIS were functionally more independent (p = 0.011)) compared with participants with tetraplegia and other AIS grades. Participants with paraplegia reported having a more active lifestyle (p = 0.040) in their home and social activities compared to those with tetraplegia. There was no significant association found between functional independence at pre-discharged and community integration one-month post-discharge of the people with SCI.ConclusionA month after discharge, there is no statistically significant relationship between community reintegration and functional independence. A measure of functional independence may not be a suitable indicator of community integration. It is proposed that to monitor a person's community integration the CIQ could be used with a measure of quality of life as this would indicate a person's contentment with their level of community integration.